Restorative Justice Distortion at The Investigation Stage in Indonesia - Kristianingsih, Ekawaty; Wijaya, Oscarius Yudhi Ari (Moestopo International Review on Social, Humanities, and Sciences, 2026)
The application of restorative justice at the investigation stage of criminal proceedings in Indonesia raises significant normative and empirical concerns. Normatively, the investigation stage is a preliminary phase aimed at identifying whether a criminal offense has occurred, not resolving disputes. Nevertheless, empirical practices show that restorative justice mechanisms are frequently applied during this stage, particularly in fraud and embezzlement cases. Police reports are often used as instruments of pressure to compel settlement, blurring the line between voluntary restoration and coercive negotiation. This study employs a qualitative literature review with a normative-empirical approach, examining statutory regulations, policy frameworks, and scholarly works published between 2015 and 2025. The findings reveal that the premature application of restorative justice at the investigation stage contradicts criminal procedural law and transforms restorative justice from a victim-centered paradigm into a tool of pragmatic case disposal. This article argues that restorative justice must be repositioned to stages where legal certainty regarding criminal liability has been established, ensuring it functions as an instrument of substantive justice rather than a coercive mechanism that bypasses due process of law.